ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN UNTUK MEMBELI MOBIL TOYOTA AVANZA (STUDI KASUS PADA PT. ASTRA INTERNATIONAL TBK AUTO 2000 MEDAN) - Purba, Betniar (UNIKA Santo Thomas, 2020)
The purpose of this study was to determine and analyze the most dominant factors influencing consumer behavior to buy Toyota Avanza cars (case study at PT Astra International Tbk Auto 2000 Medan). The benefits of research for the development of science, especially in the field of consumer behavior, as a reference in conducting further research. The number of samples is 100 respondents, the types of data used are primary and secondary data, and the method of collecting data through questionnaires and documentation, the method of data analysis is used factor analysis. From the results of research and discussion obtained the KMO Measure of Sampling Adeguacy (MSA) Figures of 0797 with a significance level of 0,000. Because the KMO value is above 0.50 and is significant at 1 percent, the data are quite feasible for further analysis using factor analysis. Component Matrix shows that the variables analyzed are not clearly included in which factors. After the rotated component matrix is performed, the twenty variables studied are clearly included in factor 1, factor 2, factor 3, factor 4 and factor 5. The dominant factors affecting consumer behavior to buy Toyota avanza in PT Astra International Auto 2000 Medan are car prices, car brands, lifestyle, income levels and experience. The most dominant factor influencing consumer behavior is the price of a car. Suggestions that are recommended should the company target and intensify marketing in the community who work as entrepreneurs. This is based on the work of entrepreneurs who demand high mobility and have strong capital in conducting transactions, especially car purchases. Affordable and rational prices need to be considered by the company. Companies can also make the payment system look lighter by collaborating with finance companies that have a good track record.